Psychological features of the cyberbullying in modern students - Potoc'ka, Ірина; Rysynec', Тетяна; Lojko, Людмила (Psychosomatic Medicine and General Practice, 2019)
One of the most pressing problems for a child to connect to the Internet is the risk of a cyberbullying attack. Cyberbullying is the latest form of aggression, which involves cruel actions aimed at harassing, harming, humiliating people with the use of information and communication means: mobile phones, e-mail, social networks, etc. For a long time, communication on the Internet has become an integral part of the life of a modern teenager. The problem is that it may carry some dangers that an adult may not suspect. This topic is quite relevant and nowadays there is a great need to investigate this phenomenon. The phenomenon of cyberbullying is manifested in various behavioral manifestations. In the smallest manifestation, there are jokes, ridicule, songs or pictures that are not even recognizable as bulling. On the other, the radical side is psychological virtual terror, which causes irreparable harm, lowers a teenager's self-esteem, makes him emotionally depressed, and can even lead to suicidal attempts. In this regard, the term "bullycide", that is, the death of a person as a result of bulling was singled out. Psychological peculiarities of manifestation and causes of aggression of modern schoolchildren have been sufficiently studied, and the phenomenon of cyberbullying has not been revealed in modern psychological scientific literature. The purpose of this study is to study the psychological features of cyberbullying in modern schoolchildren. Due to the lack of methods to investigate this phenomenon, an authoritative questionnaire for involvement in cyberbullying was created. The psychological content of the concept, the roles inherent in cyberbullying situations, the types of behavior of the persecutor, as well as the traits inherent in the pursuer, the victim and the witness of the cyberbullying are revealed. The research results describe the results of theoretical and empirical studies of psychological features of cyberbullying manifestation in modern schoolchildren, depending on age and gender. The study found that cyberbullying is the most common phenomenon among high school students. Also, empirically proved differences in the manifestations of cyberbullying students, depending on their article.